ANALYSIS OF HYDROLOGY OF THE KALIGUNG RIVER AT TEGAL - Disty Prasanty; Saihul Anwar (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2018)
ABSTRACTRivers drain water by embracing a gravitational philosophy, in which water always flows from high to low or downstream to downstream. The process of river water flow is an endless natural process, closing the hydrological cycle by restoring the river runoff to the sea. For centuries, rivers have been used as a source of clean water, meeting human needs for drinking water, sanitation, irrigation, and so on. Large rivers are dammed to store water in the wet season and use it in the dry season for various purposes.Kali Gung or Kaligung or also known as Kaligung river is a river that flows in Tegal regency, Central Java. This river is one of the largest rivers in Tegal besides Kali Ketiwon and Kali Kemiri. This river is called Kali Gung because it is tangent to the spring that comes from Mount Agung is an ancient name from Mount Slamet in pre-Islamic times in Java. Upstream or spring water Kaligung located in the north of Mount Slamet and empties to the north precisely in the sea of Java.Keywords: Hydrologycal cycle, rivers, downstream, upstream, Kaligung.